2016
DOI: 10.1111/1758-2229.12392
|View full text |Cite
|
Sign up to set email alerts
|

Remnants of marine bacterial communities can be retrieved from deep sediments in lakes of marine origin

Abstract: Some bacteria can be preserved over time in deep sediments where they persist either in dormant or slow-growing vegetative stages. Here, we hypothesized that such cells can be revived when exposed to environmental conditions similar to those before they were buried in the sediments. To test this hypothesis, we collected bacteria from sediment samples of different ages (140-8500 calibrated years before present, cal BP) from three lakes that differed in the timing of their physical isolation from the Baltic Sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…First, how microbes perceive their environment at the microscale remains poorly understood (Stocker, ), and we do not even have an accurate estimate of the total microbial diversity present in a sample (Locey & Lennon, ). Second, prokaryotes can be dispersed much longer distances and can persist out of their suitable niches (dormant or inactive but capable of resuming growth, Lennon & Jones, ) for longer times than larger organisms (Langenheder et al, ; Sebastián et al, ). This, coupled to the fact that our perception of taxa occurrence is largely dependent on the sequencing resolution (Gibbons et al, ; Ruiz‐González et al, ), explains why our understanding of the ecology and mechanisms associated with microbial cosmopolitanism, dominance or rarity is far behind that of macroorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, how microbes perceive their environment at the microscale remains poorly understood (Stocker, ), and we do not even have an accurate estimate of the total microbial diversity present in a sample (Locey & Lennon, ). Second, prokaryotes can be dispersed much longer distances and can persist out of their suitable niches (dormant or inactive but capable of resuming growth, Lennon & Jones, ) for longer times than larger organisms (Langenheder et al, ; Sebastián et al, ). This, coupled to the fact that our perception of taxa occurrence is largely dependent on the sequencing resolution (Gibbons et al, ; Ruiz‐González et al, ), explains why our understanding of the ecology and mechanisms associated with microbial cosmopolitanism, dominance or rarity is far behind that of macroorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, knowledge of the spatial distribution of individual taxa may provide insight into their persistence capacities and niche breadth, as well as into different dispersal-related processes governing their presence. This is particularly relevant in the case of prokaryotes, which are less affected by geographical barriers (e.g., Mayol et al, 2017;Reche, D'Orta, Mladenov, Winget, & Suttle, 2018;Mestre et al, 2018;Logares et al, 2018) than other organisms, and are able to persist out of their suitable niches for longer times until favourable conditions are encountered (Hervàs, Camarero, Reche, & Casamayor, 2009;Langenheder et al, 2016;Lennon & Jones, 2011;Sebastián et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Marine-freshwater transitions are suitable for studying microbial assembly mechanisms because little overlap occurs in the abundant bacterial taxa inhabiting these two ecosystems (Lozupone and Knight, 2007;Logares et al, 2009;Tamames et al, 2010;Newton et al, 2011). Nevertheless, bacteria typically found in marine environments may be recruited from the less abundant members of freshwater or sediment communities following their exposure to marine conditions (Comte et al, 2014;Langenheder et al, 2016). This observation implies that rare or dormant taxa are viable outside their preferred salinity zone and can resume active growth when environmental conditions are favourable (Sj€ ostedt et al, 2012;Lindh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has supported the existence of such microbial seed banks: For example, multiple studies have showed that the recruitment of rare bacteria can partly explain seasonal or spatial taxonomic changes within or across communities (Campbell et al, 2011;Sjöstedt et al, 2012;Caporaso et al, 2012a;Comte et al, 2014;Shade et al, 2014;Aanderud et al, 2015;Neuenschwander et al, 2015;Ruiz-González et al, 2015;Langenheder et al, 2016;Niño-García et al, 2016a). Other studies have considered the widespread dormancy found among bacteria or archaea (Jones and Lennon, 2010;Campbell et al, 2011;Hugoni et al, 2013;Aanderud et al, 2016) or the presence of core taxa that persist spatially and seasonally within or across habitat types (Caporaso et al, 2012a;Gibbons et al, 2013;Valter de Oliveira and Margis, 2015) as evidence of a seed bank.…”
Section: Introductionmentioning
confidence: 99%